Revitalizing the On-Campus Waste Bank: Promoting Community Environmental Awareness and Improving Waste Management Efficiency - Fitrianto, Achmad Room; Nawangsari, Ajeng Tita; Agustin, Riska; Arista, Setia Rini; Ramadhani, Eka Nur Wahyu Safitri; Gibbons, Nadine Elizabeth (UI Scholars Hub, 2024)
Current waste management practices often lack the reduce, reuse, and recycle principles, leading to negative effects on public health and the environment. Comprehensive and integrated waste management is needed to achieve economic benefits, health for communities, and environmental safety. This study examines community-based sustainable waste management practices in academic institutions, thus bridging the theory-practice gap and providing a significant novelty through its integration of Sharia principles into waste management practices. It focuses on the revitalization of the Sharia-based Waste Bank (BSS) at Sunan Ampel State Islamic University (UINSA) in Surabaya, Indonesia, supporting the university’s commitment to environmental sustainability and implementing quality waste management. A mixed-methods approach was employed that included surveys, focus group discussions, and interviews to assess the current waste management situation and stakeholders’ perceptions of it, as well as potential strategies for waste bank revitalization. The findings reveal a lack of awareness of and participation in sustainable practices in the campus community. It underscores the importance of integrating awareness, regulatory compliance, and community engagement as innovative approaches to waste management. This study further provides a community-based waste management model through the revitalization of BSS at UINSA, supporting the university’s commitment to environmental sustainability and implementing quality waste management. This study contributes to enhancing waste management practices at the UINSA and its surrounding communities while aligning with global sustainability goals.